Regenerative medicine in lung diseases: A systematic review - Adamič, Neža; Vengust, Modest (Frontiers in Veterinary Science, 2023)
Regenerative medicine has opened the door to the exploration of new therapeutic methods for the treatment of various diseases, especially those associated with local or general disregulation of the immune system. In pulmonary diseases, new therapeutic strategies have emerged that are aimed at restoring functional lung tissue rather than alleviating symptoms. These strategies focus on tissue regeneration using stem cells and/or their derivatives or replacement of dysfunctional tissue using biomedical engineering. Animal health can directly benefit from regenerative therapy strategies and also serve as a translational experimental model for human disease. Several clinical trials have been conducted to evaluate the effects of cellular treatment on inflammatory lung disease in animals. Data reported to date show several beneficial effects in ex vivo and in vivo models; however, our understanding of the mechanisms that regenerative therapies exert on diseased tissues remains incomplete.